Synthesis of Film Cellulose-Glycerol-Cloves Oil as Chili Packaging - Endang Widjajanti Laksono; Putri Nur Halimah (Indonesian Journal of Chemistry and Environment, 2023)
The aim of this research is to know the utilization of cellulose film with the addition of glycerol and clove oil in various variations as the best chilli packer based on mechanical properties, surface photo, water resistance test, and its effectiveness to extend the life of chilli. The production of cellulose film as packaging in this research is done by using coating method. In the coating method, variations of glycerol and clove oil were added in the ratio of (3: 1), (5: 1), (7: 1), (10: 1), and (15: 1) (v / v). The synthesized cellulose film will be characterized by functional group analysis using FTIR-ATR, mechanical test using Tensile strength, surface photo using optical microscope, cellulose film resistance test to water, and effectiveness test as chili packaging. FS Gli: Ck (3: 1) is a cellulose film with variations in the addition of glycerol and the best clove oil which has a tensile strength of 12.193 MPa, elongation of 9.761%, the most homogeneous surface photo, the greatest water resistance value 42,87, and effectiveness best cellulose film as a chilli packer.